A two-pronged approach to reduce noise levels in the neonatal intensive care unit. (July 2020) - Casey, Lara; Fucile, Sandra; Flavin, Michael; Dow, Kimberly
Abstract: Objectives: The aim of this study was to assess the efficacy of a visual noise feedback system and "quiet time" in reducing noise levels in the neonatal intensive care unit (NICU). Design: A prospective cross-sectional study was performed in a combined level II/III NICU at a Canadian tertiary care hospital. Noise levels were recorded continuously for three weeks without and then three weeks with visual noise feedback system. Noise levels were compared after one year of using visual feedback, and subsequently with the addition of two "quiet times." Results: Visual feedback reduced noise levels from 54.2 dB (95% CI 53.8–54.7 dB) to 49.4 dB (95% CI 48.9–49.8 dB; P < 0.0001) and increased the amount of time spent under 45 dB from 0 to 25% (P < 0.0001) after three weeks of use. However, this effect was not sustained at one year of visual feedback, with noise levels at 54.7 dB (95% CI 54.5–55.0 dB, P = 0.55). Quiet Time did not further reduce daily noise in the NICU (average noise levels 54.7, 95% CI 54.4–55.0 dB, P = 0.836). Conclusions: While visual noise feedback system reduced noise levels in the short term, these effects were not sustainable at one year and could not be remediated with the addition of a Quiet Time initiative. Continuing education regarding the detrimental effects of noise is paramount to ensure persistent noise reduction in the NICU. Highlights: A visual feedback warning system in the NICU reduces noise levels in the short term only. The introduction of Quiet Time does not affect average daily noise levels in the NICU. Continuing education regarding the detrimental effects of noise is paramount to ensure persistent noise reduction in the NICU.